The Strategies Applied by English Teachers in Teaching Reading Comprehension: Situation of Post Covid-19 Pandemic - Hasman; Maming, Khadijah; Nasrullah A; Muh. Syukri Asqari (Universitas Sulawesi Barat, 2023)
There are many strategies that educators can use to support successful learning in the classroom, especially for teachers of English, with all the preconditions needed for educators to use learning strategies appropriate to students' situations and circumstances that greatly depend on the situation and the problems that arise. Faced with more complex situations, with all the hassle existing in determining learning strategies, the covid-19 pandemic arrived which interrupted the application of learning strategies as students had to stay at home and wiped out the teacher-student interaction for several years after pandemic covid-19 over. By using a qualitative descriptive research method used to analyze events, phenomena, and social conditions that are well suited to what all levels of society and even the whole country are facing, namely the covid-19 pandemic. The results of this study show that The teachers' strategies applied by English teachers in teaching reading comprehension post-pandemic covid-19 is teacher-activated background knowledge of students, reading aloud together, using a dictionary to find the meaning of difficult words, and explaining again the message of the text, the last teacher asked students to answer the question of the text, teachers’ problems in teaching reading comprehension post-pandemic covid-19 the low interest of students to study English, the students making noise in the classroom, and the students being lazy, the teacher’s strategy solved the problems were teachers always motivated students to study hard, especially in English, gave advice to the students who made a noise or when they sleepy, moved the place of students when they made a noise and gave reward to the students who study hard and got high score in the class.